A35 MICROBIAL PROTEOLYTIC SIGNATURE IN ULCERATIVE COLITIS INDUCES AN INFLAMMATORY SIGNATURE IN MICROBIOTA-HUMANIZED MICE. (26th February 2020) - Galipeau, H J; Turpin, W; Caminero Fernandez, A; Santiago, A; Libertucci, J; Bermudez-Brito, M; Armstrong, S; Bedrani, L; Croitoru, K; Verdu, E
Abstract: Background: Altered gut microbiota composition has been associated with inflammatory bowel diseases (IBD) including ulcerative colitis (UC), but causality and bacterially-driven mechanisms, are unclear. Proteases within the gastrointestinal tract play a critical role in maintaining homeostasis and are tightly regulated by anti-proteases. Host-derived proteolytic imbalances have been described in IBD, including UC, however, the role of intestinal microbiota as a source of proteases and anti-proteases has largely been ignored. Aims: To study microbial proteolytic activity and intestinal microbiota profiles in a cohort of individuals at-risk for IBD, and in those individuals that develop UC at follow-up. Methods: Fecal samples were collected from healthy individuals at-risk for IBD and who went on to develop UC (pre-UC; n=14) and again after UC diagnosis (post-UC, n=10). Fecal samples from matched at-risk individuals that did not develop UC were used as healthy controls (n=52). Overall fecal proteolytic and elastolytic activity was measured. We performed metagenomics sequencing in 4 UC subjects (pre and post) and 4 matched HC using Illumina Hi-Seq from stool DNA. To investigate bacterial origin and functional significance, pregnant germ-free (GF) mice were colonized with a fecal sample from a selected UC subject (pre and post) and a matched HC. Naturally colonized litters were followed for 12 weeks, after which proteolytic activities and signs of inflammation were measured. Results: Fecal proteolytic and elastase activity was increased in pre- and post-UC samples compared to HCs. Metagenomics revealed over 20k genes were significantly different between HC and pre-UC samples, and of these, 440 related to proteases and peptidases. Increased fecal proteolytic activity, higher lipocalin levels, and increased colonic polymorphonuclear cells in colonic H&E sections was observed in pre- and post-UC colonized mice compared to HC colonized mice. Mice colonized with pre-UC microbiota showed increased mRNA expression of genes linked to immunological disease, antimicrobial and inflammatory responses (ie. Tlr2, Tlr5, Nod2, and Il1b ) as compared to HC colonized mice. Conclusions: These results suggest increased fecal proteolytic activity is observed prior to the onset and clinical diagnosis of UC in patients at-risk for IBD, and upon transfer to mice born from colonized GF dams, low-grade inflammation develops. These pathways could be developed as novel non-invasive biomarkers to monitor at-risk populations. Submitted on behalf of the CCC-GEM Project consortium. Supported by CCC GIA to EF Verdu Funding Agencies: CCC